Autonomy and Community in Learning Languages Online: A Critical Autoethnography of Teaching and Learning in COVID-19 Confinement During 2020 - Dutton, Jacqueline (Frontiers in Education, 2021)
During COVID-19 confinement 2020, there has been a massive increase in learning languages online via a variety of apps, short courses, and as part of higher education on-campus degrees converted to online learning. This study argues that attention to the balance of autonomy and community is vital to successful language learning online. An initial exploration of recent scholarship on autonomy and community in learning languages online validates this approach to evaluating the situation. The specific phenomenon of online language teaching and learning during 2020 at the University of Melbourne is then presented as an autoethnographic case study and analysed in the context of this research. In 2020, the author participated in online language learning experiences from several different perspectives. As Head of Languages, she led development of a new undergraduate certificate in languages in response to an Australian Federal Government initiative to offer significant subsidies for online language certificates in 2020. As a keen language learner, she enrolled in one of these certificates to study Italian. As a French lecturer, she converted Matters of Taste – French Eating Cultures, a highly interactive and sensory oriented on-campus subject for advanced French students, to online delivery. The autoethnographic work undertaken in this article aims to examine critically the author’s experiences of teaching and learning in 2020, assessing the advantages and disadvantages of learning languages online from positions of both teacher and learner. These experiences are triangulated with the academic and administrative leadership and coordination required to produce a schema that relates intentions to outcomes in this particularly challenging context. This study is intended to offer insights that may help language educators reflect on their various roles during COVID-19 confinement. In conclusion, this study demonstrates that negotiating the balance between autonomy and community is (still) the key to learning languages online during COVID-19 confinement in 2020.